Incidental finding of a small cell neuroendocrine carcinoma of the ureter. Issue 7 (1st August 2019) - Obi-Njoku, Obinna; Bell, Chris; Menon, Prashant Ravindran; Shergill, Iqbal
Abstract : The ureter is an extremely rare site for small cell neuroendocrine carcinoma. We present a case of this disease in a patient who presented without urological symptoms. The multidisciplinary team proposed nephroureterectomy (if fit) or watchful waiting as management. After discussion with the patient a decision in favour of watchful waiting was made. We report her case including a review of the literature, and emphasise that although small cell neuroendocrine carcinomas can be very aggressive, they can remain asymptomatic.